2014
DOI: 10.7860/jcdr/2014/10350.4853
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of B MI , Serum Leptin Levels and Lipid Profile in Patients with Skin Tags

Abstract: All the above derangements confirm that ST is cutaneous findings frequently associated with obesity and dyslipidemia. Thus follow-up of these patients with regard to the development of diseases associated with atherosclerosis may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 26 publications
0
18
0
7
Order By: Relevance
“…Another study conducted by Sari et al, found that the frequency dyslipidaemia was 59.3% [5]. A recent Indian study [19] found that mean TC levels and TC/HDL-C ratio were significantly higher in the cases than those in the control group.…”
Section: Discussionmentioning
confidence: 98%
“…Another study conducted by Sari et al, found that the frequency dyslipidaemia was 59.3% [5]. A recent Indian study [19] found that mean TC levels and TC/HDL-C ratio were significantly higher in the cases than those in the control group.…”
Section: Discussionmentioning
confidence: 98%
“…Jedna z koncepcji mówi, że mechanizm tworzenia się włókniaków jest spowodowany działaniem leptyny na jej receptory obecne w naskórku i skórze wła-ściwej [7,21]. Leptyna jest białkiem wytwarzanym głównie przez adipocyty, a jej stężenie jest wprost proporcjonalne do masy tkanki tłuszczowej [22].…”
Section: Włókniaki a Leptynaunclassified
“…Białko to bierze udział w regulacji apetytu, zmniejsza ekspresję genów kodujących enzymy odpowiedzialne za biosyntezę kwasów tłuszczowych, natomiast zwiększa ekspresję genu kodującego lipazę zależną od hormonów. Leptyna zwiększa wrażliwość tkanek na insulinę i poprawia tolerancję glukozy [7,23,24]. Ma również mitogenny wpływ na keratynocyty, przyspieszając epitelizację ran, i dlatego uznawana jest za nowy czynnik wzrostu [21,23].…”
Section: Włókniaki a Leptynaunclassified
See 2 more Smart Citations